Respuesta :
Hey there!
Okay let's look at the given values...
(-10, -6) m = -5/8
Now remember the formula we use to get an equation is called the point-slope form and it looks like this....
(y - y₁) = m(x - x₁)
Now we just substitute in the known values in for the proper variables...
(y + 6) = (-5/8)(x + 10)
y + 6 = -5x/8 - 25/4
y = -5x/8 - 49/4 <------ This is the equation you are looking for!
I hope this helps!
Please vote me for Brainliest if there is a second answer!!! ^__^
Okay let's look at the given values...
(-10, -6) m = -5/8
Now remember the formula we use to get an equation is called the point-slope form and it looks like this....
(y - y₁) = m(x - x₁)
Now we just substitute in the known values in for the proper variables...
(y + 6) = (-5/8)(x + 10)
y + 6 = -5x/8 - 25/4
y = -5x/8 - 49/4 <------ This is the equation you are looking for!
I hope this helps!
Please vote me for Brainliest if there is a second answer!!! ^__^
Answer:
[tex]y+6=-\frac{5}{8}(x+10)[/tex]
Step-by-step explanation:
We are given that the line passing through a point (-10,-6) and slope of line,m=[tex]-\frac{5}{8}[/tex]
We have to find the equation of line in point-slope form for the line.
We know that
The equation of line which is passing through the point [tex](x_1,y_1)[/tex] with slope m is given by
Point-slope form:[tex]y-y_1=m(x-x_1)[/tex]
We have [tex]x_1=-10,y=-6,m=-\frac{5}{8}[/tex]
Using the formula
The equation of line which is passing through the point (-10,-6) with slope -5/8
[tex]y-(-6)=-\frac{5}{8}(x-(-10))[/tex]
[tex]y+6=-\frac{5}{8}(x+10)[/tex]